Pengaruh Waktu Pemerahan dan Tingkat Laktasi terhadap Kualitas Susu Sapi Perah Peranakan Fries Holstein - Mardalena, Mardalena (Fakultas Peternakan Universitas Jambi, 2008)
This study intended to know the difference of milk quality result of pressing out of evening and morning at level of lactation (I, II and III) of Fries Holstein dairy cattle. Experimental design used in this experiment was Complete Randomized Design (CRD) Factorial 2x3 Pattern by 10 times replication. The result indicated that quality of milk at pressing out of morning were fat rate (3,17%), dry materials rate ( 12,206%) and protein rate ( 3,583%)was lower than pressing out of evening which were fat rate ( 3,69%), dry materials rate ( 12,527%) and protein rate ( 3,613%). Conclusion of this research was the quality of milk when pressing out morning lower than evening. Level of lactation didn’t influence the quality of milk.